CAMERRA: An analysis tool for the computation of conformational dynamics by evaluating residue–residue associations. Issue 20 (21st February 2018) - Johnson, Quentin R.; Lindsay, Richard J.; Shen, Tongye
Abstract : A computational method which extracts the dominant motions from an ensemble of biomolecular conformations via a correlation analysis of residue–residue contacts is presented. The algorithm first renders the structural information into contact matrices, then constructs the collective modes based on the correlated dynamics of a selected set of dynamic contacts. Associated programs can bridge the results for further visualization using graphics software. The aim of this method is to provide an analysis of conformations of biopolymers from the contact viewpoint. It may assist a systematical uncovering of conformational switching mechanisms existing in proteins and biopolymer systems in general by statistical analysis of simulation snapshots. In contrast to conventional correlation analyses of Cartesian coordinates (such as distance covariance analysis and Cartesian principal component analysis), this program also provides an alternative way to locate essential collective motions in general. Herein, we detail the algorithm in a stepwise manner and comment on the importance of the method as applied to decoding allosteric mechanisms. © 2018 Wiley Periodicals, Inc. Abstract : CAMERRA reveals concerted motions by tracking the correlated contact dynamics between residues of a protein complex. The displacement mode shows residue–residue contact breaking (red cylinders) and forming (blue). In a further simplified cartoon illustration, each circle represents either an amino acid residue or a ligand. Two ligands " i " and " l " may communicate with each other via their respective binding proteins using a series of contact dynamics, involving residues, such as " j " and " k ."